Variable gain amplifier - Hoo, Swee Chuen. (2008)
A detailed study of various variable gain topologies is presented in this report. A Variable Gain Amplifier (VGA) with an exponential gain control characteristic is desired in Automatic Gain Control (AGC) application. Thus, a metal-oxidesemiconductor (MOS) variable gain amplifier with linear in dB characteristic was designed. The voltage gain or transconductor of the VGA can be varying by a control voltage. This amplifier, based on complementary MOS (CMOS) transistors operating in strong inversion, is composed of exponential voltage generator block, four quadrant analog multiplier and tranresistance output stage.